2021
DOI: 10.3390/en14010200
|View full text |Cite
|
Sign up to set email alerts
|

Acoustic Emission Characteristics and Joint Nonlinear Mechanical Response of Rock Masses under Uniaxial Compression

Abstract: The joint arrangement in rock masses is the critical factor controlling the stability of rock structures in underground geotechnical engineering. In this study, the influence of the joint inclination angle on the mechanical behavior of jointed rock masses under uniaxial compression was investigated. Physical model laboratory experiments were conducted on jointed specimens with a single pre-existing flaw inclined at 0°, 30°, 45°, 60°, and 90° and on intact specimens. The acoustic emission (AE) signals were moni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 41 publications
0
6
0
Order By: Relevance
“…Therefore, the research results showed certain similarity with the numerical test results in this paper. The laboratory physical test results of Feng et al (2021), Song et al (2020), Li S. et al (2019), and Li D. et al (2019 and the PFC2D (particle flow code in two dimensions) numerical test results of Wen et al (2016) also showed that, under uniaxial compression, the AE peak of a single joint specimen with different joint dip angles roughly appeared near the peak stress of the stress-strain curve. However, when the joint dip angles were 30 °and 45 °, the AE results of the numerical tests of Wen et al (2016) did not obviously show this characteristic, which may be related to the numerical test method used.…”
Section: Effects Of Different Model Boundaries and Confining Pressures On The Ae Of Jointed Rock Massmentioning
confidence: 93%
“…Therefore, the research results showed certain similarity with the numerical test results in this paper. The laboratory physical test results of Feng et al (2021), Song et al (2020), Li S. et al (2019), and Li D. et al (2019 and the PFC2D (particle flow code in two dimensions) numerical test results of Wen et al (2016) also showed that, under uniaxial compression, the AE peak of a single joint specimen with different joint dip angles roughly appeared near the peak stress of the stress-strain curve. However, when the joint dip angles were 30 °and 45 °, the AE results of the numerical tests of Wen et al (2016) did not obviously show this characteristic, which may be related to the numerical test method used.…”
Section: Effects Of Different Model Boundaries and Confining Pressures On The Ae Of Jointed Rock Massmentioning
confidence: 93%
“…Then, 0.3 mm of emery steel wire was used to go through the small hole, and the joint with a length of 20mm and an average thickness of 0.5mm-0.7mm was sawed out. Joint dip angle β references (Feng et al 2021) select 0°, 30°, 45°, 60° and 90°. After the test specimens are made, the test specimens shall be numbered in groups of 3 test specimens each.…”
Section: Preparation Of Specimensmentioning
confidence: 99%
“…While these studies have confirmed the practicality and reliability of 2D simplified models in some respects, research on the mechanical behaviors of jointed rock in different dimensions, especially the influence of the failure mode and crack initiation mechanism of jointed rock, is still limited. Natural rock formations always contain many defects and joints, and the study of crack initiation mechanisms is of great significance to future experimental research on jointed rock and even the unstable fracture analysis of engineering rock formations [19][20][21].…”
Section: Introductionmentioning
confidence: 99%